Lithografie en Lay-out. Offset-handpersdrukkerij op achterzijde. Uit een brochure gewijd aan het bedrijf (1948)
Lithografie en Lay-out. Offset-handpersdrukkerij op achterzijde. Uit een brochure gewijd aan het bedrijf.